A scoping review of the experience of implementing population testing for SARS-CoV-2. (September 2021) - Foster, C.R.; Campbell, F.; Blank, L.; Cantrell, A.J.; Black, M.; Lee, A.C.K.
Abstract: Objectives: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) – also known as the coronavirus disease (COVID-19) – pandemic has led to the swift introduction of population testing programmes in many countries across the world, using testing modalities such as drive-through, walk-through, mobile and home visiting programmes. Here, we provide an overview of the literature describing the experience of implementing population testing for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Study design: Scoping review. Methods: We conducted a scoping review using Embase, Medline and the Cochrane library in addition to a grey literature search. We identified indicators relevant to process, quality and resource outcomes related to each testing modality. Results: In total, 2999 titles were identified from the academic literature and the grey literature search, of which 22 were relevant. Most studies were from the USA and the Republic of Korea. Drive-through testing centres were the most common testing modality evaluated and these provided a rapid method of testing whilst minimising resource use. Conclusions: The evidence base for population testing lacks high quality studies, however, the literature provides evaluations of the advantages and limitations of different testing modalities. There is a need for robust evidence in this area to ensure that testing is deployed in a safe and effective manner in response to the COVID-19 pandemic.